A Scoping Review of Tinnitus Research Undertaken by New Zealand Researchers: Aotearoa – An International Hotspot for Tinnitus Innovation and Collaboration - Searchfield, Grant; Adhia, Divya; Barde, Amit; De Ridder, Dirk; Doborjeh, Maryam; Doborjeh, Zohreh; Goodey, Ronald; Maslin, Michael RD; Sanders, Phil; Smith, Paul F; Zheng, Yiwen (Informa UK Limited, 2024)
Tinnitus is a very common oto-neurological disorder of the perception of sound when no sound is present. To improve understanding of the scope, strengths and weaknesses of New Zealand tinnitus research, a critical scoping review was undertaken. The aim was to help develop priorities for future research. A review of the literature was undertaken using a 6-stage scoping review framework of Scopus and Pub Med were searched in May 2023 with the combination of following key word [Tinnitus] and country of affiliation [New Zealand]. The search of PubMed resulted in 198 articles and that of Scopus 337 articles. After initial consideration of title relevance to the study (165 from PubMed and 196 from Scopus) removal of duplicates and after reading the articles and adding from references, 208 studies were chosen for charting of data. Nine themes were identified and described: A. Epidemiology; B. Models; C. Studies in animals; D. Mechanisms; E. Assessment and prognosis; F. Pharmacotherapy; G. Neuromodulation; H. Sensory therapies; I. Clinical practice. An urgent priority for future tinnitus research in NZ must be to address the absence of cultural and ethnic diversity in participants and consideration of traditional knowledge.
Keywords: Innovation; Mechanisms; New Zealand; Therapy; Tinnitus; Treatment; 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; General Science & Technology